Prediksi Laju Erosi Baja API 5L pada Pipa Siku Minyak dan Gas Menggunakan Komputasi Fluida - Hendy Roesma Wardhana; Atik Setyani; Sudaryanto Sudaryanto (Journal of Metallurgical Engineering and Processing Technology, 2023)
A large amount of oil and gas production needs to be followed by optimal pipeline maintenance. Most cases of pipe leaks are sudden in nature that able to cause losses over a long period of time. The gas consisting of sand particles able to increase erosion rate, especially at the pipe elbows. Cases of pipe leaks able to be prevented through routine inspections based on accurate erosion rate predictions. This study aims to predict the erosion rate of elbow piping systems using computational fluid simulations. The pipe material used is API 5L x60 and x70 steel. The simulation environment is arranged in such a way as to the reality on the oil and gas field. Methane gas containing sand particles with a hardness of 1100 HV is applied to this simulation. The simulation results prove that there is a relationship between the erosion rate, pipe hardness, and impact angle.Keywords: Erosion Rate Predictions, Elbow Pipe, and Hardness Pipe